Suboptimal Solutions for Time Varying Time Delayed MPC Controllers - Mumcu, T. Veli; Gulez, K. (KAUNAS UNIV TECHNOLOGY, 2014)
Model Predictive Control (MPC) with constraints is still an interesting subject and offers many problems to work on. This study basically aims to understand the optimization process and the decrease of convex quadratic costs in a single model predictive controller. For those processes where the system dynamics change so slowly it is essential to obtain the control law as soon as possible to minimize the time delay on the controller side. This study proposes an early termination of the optimization process and the suboptimal solution to the quadratic programming. To define the early termination in the following chapters it is discussed and explained when, where. The implementation of the strategy is also illustrated with a case study and it is compared to the LQR controller for the regulator problem.
Keywords: Model predictive control; MPC; time varying time delay; quadratic programming; MODEL-PREDICTIVE CONTROL; SYSTEMS; Engineering